In the pitfall of expectations: An exploratory analysis of stressors in elite rhythmic gymnastics - Kovács, Krisztina; Kéringer, Johanna; Rácz, József; Gyömbér, Noémi; Németh, Krisztina (Frontiers in Psychology, 2022)
The present study explored the types of stressors faced by rhythmic gymnastics athletes, their parents, and coaches. Semi-structured interviews with 12 participants — four gymnasts, five coaches, and three parents — were analyzed using reflexive thematic analysis in a theory-driven framework. The categorizations of sport-related stressors for the parents, coaches, and gymnasts were based on existing theories. The results showed that both the gymnasts and the coaches predominantly noted mastery-avoidance goals in terms of performance, while the interviews with parents mostly indicated performance-avoidance goals. All three groups of participants consistently reported a detrimental atmosphere in rhythmic gymnastics. For instance, they emphasized the stress related to inadequate communication between the concerned parties. Moreover, all parties believed that having a lean body was linked to success in the competitive world of rhythmic gymnastics. The present study provides insight into some of the potential major stressors and the related subjective experiences affecting athletes socializing in the same sporting environment.